The Importance of Systematic Analysis in the Drying Process of Fruit and Vegetable Pastilla - Kholikov, Mukhriddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: This article provides information on the significance of systematic analysis in the drying process of fruit and vegetable paste, as well as recommendations for the development of high-quality products for the food industry. It emphasizes the importance of using advanced production technologies and modern methods of processing and storing products in order to achieve sustainable development in the fruit and vegetable industry. The article discusses the benefits of scientific analysis in improving the quality of agricultural products and emphasizes the need for systematic analysis in the production process. It also presents an algorithm for using systematic analysis in drying fruit and vegetable pastes, as well as the main features of the processing process. By following these recommendations, producers can ensure the production of high-quality semi-finished products enriched with biological additives, which are essential for the food industry. Furthermore, the use of effective methods of drying fruits and vegetables can help preserve their nutritional value and extend their shelf life.Justifying the optimal drying parameters for fruit and vegetable pastilles in an innovative way, we have determined a highly efficient and energy-saving drying process, as well as technical and economic indicators for producing various dried pastille compositions based on the high moisture content of fruits and vegetables. This process helps to reduce the waste of raw materials during processing.